Political reconciliation in Timor Leste, Solomon Islands and Bougainville: the dark side of hybridity. Issue 2 (3rd March 2016) - Wallis, Joanne; Jeffery, Renee; Kent, Lia
ABSTRACT: In recent years, the study and practice of political reconciliation has experienced a turn to hybridity. This turn has been defined by the increased rate at which liberal international and local peacebuilding practices, and their underlying ideas, have become merged, integrated or co-located in time and space. While hybrid approaches to reconciliation have been praised as an effective means of engaging local populations in peacebuilding operations, little attention has been paid to examining whether or not they also bring unintended negative consequences. Drawing on the cases of Timor Leste, Solomon Islands and Bougainville, this article examines the potentially dark side of hybridity. It demonstrates that, in each of these cases, hybrid approaches to political reconciliation have brought both positive and negative consequences. On the positive side of the equation, hybridity has seen imported international approaches to reconciliation adapted to meet local demands and ensure resonance with local populations. On the negative side, however, the misappropriation and instrumentalisation of local practices within hybrid approaches has served to damage their legitimacy and to jeopardise their contributions to reconciliation. The article thus concludes that the existence and extent of this dark side necessitates a re-evaluation of how hybrid approaches to political reconciliation are planned and implemented.